2003
DOI: 10.1042/bj20020707
|View full text |Cite
|
Sign up to set email alerts
|

A functional activating protein 1 (AP-1) site regulates matrix metalloproteinase 2 (MMP-2) transcription by cardiac cells through interactions with JunB-Fra1 and JunB-FosB heterodimers

Abstract: Enhanced synthesis of a specific matrix metalloproteinase, MMP-2, has been demonstrated in experimental models of ventricular failure and in cardiac extracts from patients with ischaemic cardiomyopathy. Cultured neonatal rat cardiac fibroblasts and myocytes were used to analyse the determinants of MMP-2 synthesis, including the effects of hypoxia. Culture of rat cardiac fibroblasts for 24 h in 1 % oxygen enhanced MMP-2 synthesis by more than 5-fold and augmented the MMP-2 synthetic responses of these cells to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(158 citation statements)
references
References 47 publications
4
150
2
2
Order By: Relevance
“…Functional analysis of the gene promoters of MMP-2 and MMP-9 has allowed identification of several binding domains for transcription factors such as AP-1 and NF-B. [45][46][47] Promoters of genes encoding TIMP-1 and TIMP-2 also contain consensus sequences for AP-1. 48,49 uPA expression is regulated through AP-1 binding sites in human prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis of the gene promoters of MMP-2 and MMP-9 has allowed identification of several binding domains for transcription factors such as AP-1 and NF-B. [45][46][47] Promoters of genes encoding TIMP-1 and TIMP-2 also contain consensus sequences for AP-1. 48,49 uPA expression is regulated through AP-1 binding sites in human prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the levels of col ␣1(III) and TGF␤1 expression did not appear to differ between groups (␤-actin expression is shown as an internal control). Whereas IL-1 is a potentially important upstream regulator of MMP-2 and -9 (16,17), MMPs form a complex interacting network in the context of MI and are also subject to regulation by hypoxia and peptide growth factors; often through common regulatory elements such as AP-1 (16,17). Interestingly, unloading the myocardium with an LV assist device in patients with ischemic cardiomyopathy results in decreased MMP-2 levels (40), and a similar effect after SkM implantation is a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase (MMP) types 2 and 9 (MMP-2͞-9) are key gelatinases shown to be directly involved in post-MI ECM turnover (15). IL-1 stimulates expression of MMP-2 in ischemic cardiac fibroblasts and is a regulator of MMP-9 (16,17). No studies, however, have exploited sustained IL-1 inhibition as a means to target adverse post-MI remodeling.…”
mentioning
confidence: 99%
“…In contrast, the proximal Sp-1 and AP-2 sites at Ϫ90 to Ϫ50 bp are sufficient for constitutive MMP-2 transcription in astrocytoma cell lines (9). We recently demonstrated that activation and binding of activating protein-1 (AP-1) family transcription factors, specifically Fra1-JunB and FosB-JunB heterodimers, to a noncanonical AP-1 site (located at Ϫ1,392 bp relative to the start site of translation) are essential for hypoxia-induced MMP-2 transcription in cardiac fibroblasts (10).…”
mentioning
confidence: 99%